Antenna Characteristics Contributions to the Improvement of UWB Real-Time Locating Systems’ Reading Range and Multipath Mitigation - Amina Benouakta; Fabien Ferrero; Leonardo Lizzi; Robert Staraj (IEEE Access, 2023)
Indoor object localization and positioning is part of the space-awareness concept which has seen a rising popularity in recent Internet of Things (IoT) research and applications. This article presents a novel method to improve the localization performance of ultra-wide band (UWB) real-time locating systems (RTLS) by improving the transmitting and receiving reader and tag antennas. Patch directional UWB antennas with relatively higher gain compared to the generally used standard omnidirectional monopole UWB antennas have been exploited to achieve a larger localization range. Furthermore, the patch antennas were designed to have wideband circular polarization to achieve two objectives: a received power independent of the orientation of the tagged objects that need to be detected, and the filtering of unwanted multipath signals. A measurement campaign was conducted using a commercially available RTLS with conventional antennas and then with the newly designed antennas. A comparison between the localization results of the two antenna types demonstrates an improved range with almost 100 m difference, received power independent of tag orientation, and increased multipath mitigation with the directional circularly polarized antennas.